Performance Comparison between Recycled Single Stage and Double Stage Hydrocyclones - Raheem, Mohannad A.; F. Qassim, Raghad (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
This research presents a comparison of performance between recycled single stage and double stage hydrocyclones in separating water from water/kerosene emulsion. The comparison included several factors such as: inlet flow rate (3,5,7,9, and 11 L/min), water feed concentration (5% and 15% by volume), and split ratio (0.1 and 0.9). The comparison extended to include the recycle operation; once and twice recycles. The results showed that increasing flow rate as well as the split ratio enhancing the separation efficiency for the two modes of operation. On the contrary, reducing the feed concentration gave high efficiencies for the modes. The operation with two cycles was more efficient than one cycle. The maximum obtained efficiencies were 97% and 97.5% at 5% concentration, 11 L/min, and 0.9 split ratio for twice recycled single stage and double stage hydrocyclones, respectively. The pressure drop was the same for the two modes of operation. It was concluded that using recycled single stage hydrocyclone was more economical since it reduced the cost of additional hydrocyclone.